Population genetic structure of the ascidian Styela rustica at Kongsfjord, Svalbard, Arctic Ocean - Demarchi, Maria Milagros; Chiappero, Marina Beatriz; Laudien, Jürgen; Sahade, Ricardo Jose (Journal of Experimental Marine Biology and Ecology)
The actual Arctic biota shows a strong affinity with that of the Boreal Atlantic and Pacific ones, as a result of an active recolonization process after the Quaternary glaciations. The geographic distribution of sessile species is usually linked to larvae dispersive capabilities which can be directly related with time spent in the plankton. Ascidians larvae are lecitothorphic and short-lived, which suggest that ascidians could be not efficient dispersers. However, the solitary ascidian Styela rustica (Linnaeus, 1767) (Tunicata, Ascidiacea) shows a wide distribution pattern from the North Atlantic to the Arctic that, together with the relatively recent colonization of the Arctic system could indicate that this species efficiently disperses and colonizes new habitats. In this study we used ISSR-PCR markers to study the genetic structure of five populations of the ascidian Styela rustica at Kongsfjorden, west Spitsbergen (Svalbard archipelago). We analyzed whether this species presents a low genetic structure, as can be expected due to the historical process of recent post glaciations colonization, or if there is genetic differentiation at a local scale, caused by short-lived larvae and limited dispersal potential. The genetic diversity in each population assessed using the marker diversity index (M) ranged from 0.288 to 0.324. Population HN, situated close to a fast retreating glacier, showed the lowest diversity. Processes associated with deglatiation (icebergs calving from the glacier that scour the benthos and the increment of inorganic particulate matter on the water column) would drive to reduced population sizes and explain the reduced genetic variability observed in the HN population with respect to the others in the fjord. This suggests a possible linkage with the global warming process. Although the weak genetic structure found among the studied populations could indicate a founder effect, the genetic landscape shape analysis together with a positive relationship between genetic and geographic distances ...